Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek INDONESIA - Widiyasrani, Syaniatus; Dewi Astuti, Tutut (Jurnal Ilmiah Raflesia Akuntansi, 2023)
This research aims to investigate the impact of the Current Ratio, Debt to Asset Ratio, Total Asset Turnover, and Net Profit Margin on Profit Growth in Food and Beverage Companies Listed on the Indonesia Stock Exchange for 2019–2021. Purposive sampling methods were used in this study's sampling, which resulted in samples from 18 companies. The secondary data used in this study was obtained from financial statements filed on the Indonesia Stock Exchange. Descriptive statistical tests, traditional assumption testing, multiple linear regression analysis, and hypothesis tests are the research steps used in this work. The findings of this research demonstrate that the Current Ratio, Debt to Asset Ratio, Total Asset Turnover, and Net Profit Margin have impact on profit growth.